2000
DOI: 10.1016/s0370-2693(00)00533-5
|View full text |Cite
|
Sign up to set email alerts
|

S-wave η′-proton FSI; phenomenological analysis of near-threshold production of π0, η, and η′ mesons in proton-proton collisions

Abstract: We describe a novel technique for comparing total cross sections for the reactions pp → ppπ 0 , pp → ppη, and pp → ppη ′ close to threshold. The initial and final state proton-proton interactions are factored out of the total cross section, and the dependence of this reduced cross section on the volume of phase space is discussed. Different models of the proton-proton interaction are compared. We argue that the scattering length of the S-wave η ′ -proton 1 interaction is of the order of 0.1 fm. PACS: 13.60. Le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 33 publications
(72 reference statements)
0
24
0
Order By: Relevance
“…Since the enhancement is similar in η and η case [14], and the strength of proton-η and proton-η interaction seems to be different [12], one can conclude that the observed enhancement is not caused by a proton-meson interaction, especially that calculations assuming a significant contribution of Pwave in the final state [70], and models including energy dependence of the production amplitude [71,72], reproduce the data within error bars. Therefore, the determination of the spin observables and extraction of the contribution from the higher partial waves is mandatory for the understanding of the observed enhancements in the discussed invariant mass spectra.…”
Section: Threshold Production Of the η-Nucelon-nucleon And η -Nucleonmentioning
confidence: 67%
See 4 more Smart Citations
“…Since the enhancement is similar in η and η case [14], and the strength of proton-η and proton-η interaction seems to be different [12], one can conclude that the observed enhancement is not caused by a proton-meson interaction, especially that calculations assuming a significant contribution of Pwave in the final state [70], and models including energy dependence of the production amplitude [71,72], reproduce the data within error bars. Therefore, the determination of the spin observables and extraction of the contribution from the higher partial waves is mandatory for the understanding of the observed enhancements in the discussed invariant mass spectra.…”
Section: Threshold Production Of the η-Nucelon-nucleon And η -Nucleonmentioning
confidence: 67%
“…Based on the comparison of the shape of the excitation functions for the pp → ppη and pp → ppη reactions it was concluded that the p − η interaction is much stronger than the p − η [12]. At first, the small values of the cross sections for the pp → ppη reaction [47] were even interpreted as an indication of the p − η repulsive interaction [52].…”
Section: Threshold Production Of the η-Nucelon-nucleon And η -Nucleonmentioning
confidence: 99%
See 3 more Smart Citations